Post-tenure faculty review and renewal II : (Anker Pub. Co., 2004)
A joint publication from the American Association for Higher Education’s New Pathways Project and Anker Publishing Company, this book is the second in a series on review, renewal, and vitality of tenured faculty. Discussed here is how to report the results of post-tenure review responsibly, accurately, and effectively. Because post-tenure review policy in higher education is a relatively young phenomenon, few examples are available of effective and practical ways for campuses and systems to assess their policies, report on results, and reflect on their meaning. This volume fills provides guidelines for placing data in perspective and creating knowledge that leads to wise policymaking and institutional learning. Providing examples of how this can be accomplished, the authors also supply extensive appendices that contain examples of data collection and forms, comprehensive reports, and implementation studies. This is an invaluable guide to those in the field who are grappling with how to track, report, and use information on the results of tenured faculty review in a realistic, reflective, and practical way.